Maastrichtse industriëlen en het Belgische annexisme in de jaren 1918–1919 - Beaumont, Eddy de (Studies over de sociaal-economische geschiedenis van Limburg/Jaarboek van het Sociaal Historisch Centrum voor Limburg, 2023)
Abstract: „During and immediately after the First World War the Belgian government developed plans to annex parts of the Netherlands after the war, such as the province of Limburg. How did industrialists in the capital Maastricht respond to these Belgium goals? In this article, I explore the perspectives of an industrialist, a state detective and an economist in this matter. The industrialist was a fierce opponent of annexation, while the state detective was convinced that annexionists, those who were in favour of annexation, should mainly be found among major industrialists. The economist, on the other hand, did not rule out the possibility that some of Maastricht’s traders and industrialists would prefer a connection with Belgium. How did they come to these conclusions and to what extent did their considerations and other sources provide an answer to the research question of this article? Taking both gossip and facts into account, we may conclude that indeed there could have been traders and industrialists who supported the Belgian aspirations and preferred to join Belgium. However, the general claim that, in Maastricht especially, major industrialists were in favour of annexation lacks any factual evidence.“
Keywords: Annexion; Erster Weltkrieg; Industrie; Maastricht; Provinz Limburg (Niederlande); Widerstand